Rehabilitation of a Child with Neonatal Brachial Plexus Palsy: Case Report Described by Parents - Fátima Frade; Lurdes Neves; Fátima Florindo-Silva; Juan Gómez-Salgado; Lia Jacobsohn; João Frade (Children, 2022)
This paper presents a case report of a child with Neonatal Brachial Plexus Palsy on the right arm, with C5, C6, and C7 nerve injuries. The symptoms presented at birth and at the time of diagnosis were absence of movement in the right arm but with mobility of the fingers; internal rotation of the injured limb with elbow extension; active flexion of the wrist and fingers; and ulnar deviation of the hand. The rehabilitation plan followed the conservative approach and included different intervention strategies (passive and active mobilisation, kinesio tape, use of splints, bimanual stimulation, etc.) carried out by the occupational therapist and the physical therapist. The rehabilitation allowed the child to have a functional limb for daily activities, with bimanual motor integration and coordination; passive and active range of motion in the different joints except for pronation, sensibility, and maintained strength. In conclusion, it can be said that this case report describes a set of rehabilitation strategies that were used in the conservative treatment of a child with NBPP and the functional gains they allowed. Early intervention, parental involvement in the rehabilitation process, and continuous follow-up of the child favoured the prognosis and allowed the prevention of functional sequelae of the limb.